Higher glandular trichome density in tomato leaflets and repellence to spider mites - Maluf, Wilson Roberto; Inoue, Irene Fumi; Ferreira, Raphael de Paula Duarte; Gomes, Luiz Antonio Augusto; Castro, Evaristo Mauro de; Cardoso, Maria das Graças (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the feasibility of selection for higher glandular trichome densities, as an indirect criterion of selection for increasing repellence to spider mites Tetranychus urticae, in tomato populations derived from an interspecific cross between Lycopersicon esculentum x L. hirsutum var. glabratum PI 134417. Trichome densities were evaluated in 19 genotypes, including 12 from advanced backcross populations, derived from the original cross L. esculentum x L. hirsutum var. glabratum PI 134417. Counts were made both on the adaxial and abaxial leaf surfaces, and trichomes were classified into glandular types IV and VI, other glandular types (types I+VII), and nonglandular types. Mite repellence was measured by distances walked by mites onto the tomato leaf surface after 20, 40 and 60 min. Spider mite repellence biotests indicated that higher densities of glandular trichomes (especially type VI) decreased the distances walked by the mites onto the tomato leaf surface. Selection of plants with higher densities of glandular trichomes can be an efficient criterion to obtain tomato genotypes with higher resistance (repellence) to spider mites.